2022
DOI: 10.1109/jstqe.2021.3114316
|View full text |Cite
|
Sign up to set email alerts
|

Material Gain in Polar GaInN and AlGaN Quantum Wells: How to Overcome the ‘Dead’ Width for Light Emitters in These QW Systems?

Abstract: Abstract-Polar GaInN and AlGaN quantum wells (QWs) are widely used in light emitting diodes and laser diodes (LDs). However, the widths of such QWs are usually limited to a few nanometers in order to ensure a sufficiently large overlap between the wave functions of the ground electron and the ground hole state. By increasing the QW width we enter the area of 'dead' width where, the overlap of the electron and hole wave functions decreases almost to zero and the luminescence efficiency drastically deteriorates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Therefore, the so‐called “dead width” is observed for material gain for polar QWs. [ 32 ] To design an InGaN well, it is best to make it thin, then the electric field is not screened, or very wide. In such a situation, the electric field is screened and lasering has a different character than for a thin one.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the so‐called “dead width” is observed for material gain for polar QWs. [ 32 ] To design an InGaN well, it is best to make it thin, then the electric field is not screened, or very wide. In such a situation, the electric field is screened and lasering has a different character than for a thin one.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] In contrast, lasing for wide InGaN QWs has been demonstrated experimentally. [29][30][31][32] In addition, it has been shown that there is a "dead" width for which it is difficult to achieve a positive material gain. [32] For InGaN QWs, this width is in the range of 4-8 nm, and above 8 nm, it is again easier to obtain a positive material gain.…”
Section: Doi: 101002/apxr202200107mentioning
confidence: 99%
See 3 more Smart Citations